Promoting reciprocal interactions via peer incidental teaching. - McGee, G G (1992)
This study evaluated peer incidental teaching as a strategy for increasing reciprocal peer interactions by children with autism. Three typical preschoolers were trained as peer tutors for 3 young children with autism. During a classroom free-play session, peer tutors used incidental teaching to obtain verbal labels of preferred toys by children with autism. A multiple baseline across the 3 target children showed replicated positive effects of the intervention. Adult supervision and assistance were then faded systematically, with resulting maintenance of increased reciprocal interactions. Multiple measures of the extent and limits of generalization suggested that 1 child increased interactions in free-play periods throughout the day, but none of the children showed increases at lunch. Teacher and peer ratings supported the social validity of positive findings.